The least squares concept in reducing noisy signal of single-beam acoustic systems: Ocean depth measurement to support maritime defense systems - Annisa Risda Alivia; Syasya Qonita Azizah; Alok Shukla (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2025)
Indonesia's vast ocean territory presents both opportunities and security challenges, requiring robust maritime defense. Effective sea defense includes surface patrols with naval vessels and aircraft, alongside underwater surveillance using submarines and detection systems. Advanced acoustic technology, such as Single Beam Echo Sounder (SBES) sonar, is essential for underwater depth measurement. However, environmental noise often disrupts sonar recordings, necessitating noise reduction techniques. This study applies the Least Mean Square (LMS) filter, an adaptive algorithm that adjusts filter coefficients based on error minimization. Its real-time adaptability enhances noise suppression, improving sonar signal quality. The results indicate that the LMS filter achieves an optimal Signal-to-Noise Ratio (SNR) of 6.7248 dB, surpassing other methods. Furthermore, it accurately identifies signal delays, crucial for precise depth measurement. Enhancing underwater acoustic technology through LMS filtering supports improved hydrographic surveys, benefiting scientific research, commercial navigation, and military operations in securing Indonesia’s maritime domain.